Pengaruh Celebrity Endorser dan Brand Trust Terhadap Minat Beli Produk Smartphone pada Mahasiswa Perguruan Tinggi Negeri di Kota Malang - Fiorano Coren Qolbi Torana; Rena Feri Wijayanti; Yulis Nurul Aini (Jurnal Ilmu Sosial dan Humaniora, 2026)
Rapid technological advancements have spurred the emergence of modern smartphones, including the Samsung brand, which is among the most popular in Indonesia. However, sales figures—particularly in Indonesia—have not shown significant growth. This study aims to analyze the influence of celebrity endorsers and brand trust on the purchase intention for Samsung smartphones among public university students in Malang City. A quantitative approach utilizing explanatory research was employed, involving 100 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression, incorporating both partial and simultaneous hypothesis testing. The results indicate that celebrity endorsers and brand trust have a significant influence on purchase intention. Therefore, prioritizing synergistic celebrity endorsements and strong brand trust is essential to boosting purchase intention.